ANALISIS 4K KARYAWAN TENAGA PENDIDIK - Edi Siregar (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2021)
The research was conducted to test and analyze the effect of competence, commitment and compensation on employee performance. This study used a survey method with a questionnaire as the main instrument. The populations of this study were 89 employees, with a census method where all members of the population were sampled. Data analysis was performed using regression analysis, hypothesis testing through f test and t test. The results of the analysis found that there is a significant relationship and influence both partially and simultaneously between competence, commitment and compensation with employee performance